THE RELATIONSHIP MODEL OF FEAR OF COVID-19, TRAVEL ANXIETY, AND RISK ATTITUDE TOWARD TRAVEL INTENTION IN THE NEW NORMAL ERA: A STUDY OF MARINE TOURISM IN THE EASTERN SALIENT OF JAVA, INDONESIA - Verinita, Verinita; Suryaningsih, Ika Barokah; Pratama, Mohamad Dito; Susanto, Arnis Budi (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2023)
The COVID-19 pandemic had influenced the global economy, including Indonesia"™s tourism industry. The inability to mitigate these challenges had substantially jeopardized the sustainability of tourism, with social and economic consequences. This present study examines a case study of marine tourism in the eastern salient of Java, one of the most popular places in Java Island, to determine the relationship between fear of COVID-19, travel anxiety, and risk attitude toward travel intention. This study employed a quantitative method. The data was collected through surveys distributed online via google form and was analyzed using structural equation modeling "“ partial least square (SEM-PLS) in SmartPLS 3.0. The results show that the fear of COVID-19 has a positive impact on the travel anxiety, but not on the risk attitude; the travel anxiety has a positive impact on both the risk attitude and travel intention; the risk attitude has a positive impact on the travel intention, but the fear of COVID-19 does not.  The travel anxiety has a significant impact on the risk attitude and travel intention, while the travel anxiety has no significant impact on the risk attitude and travel intention. These findings suggest the Ministry of Tourism and Creative Economy of the Republic of Indonesia need to evaluate and monitor the operation of tourism destinations, as well as continuing to disseminate information about safe travel during the new normal era.JEL: Z33, M31.